2012
DOI: 10.5505/tjh.2012.07769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fibrin Sealants and Tissue Adhesives in Oral Surgery for Patients with Bleeding Disorders

Abstract: Objective: The aim of this study was to evaluate the efficiency of two local hemostatic agents administered with apreoperative dose of replacement therapy in patients with bleeding disorders undergoing oral surgery.Material and Methods: The study included 21 patients that were randomly divided into 3 groups. Patients in Group1 (n = 7) received preoperative replacement therapy and postoperative fibrin sealant applied to the surgical site. Patientsin Group 2 (n = 7) received preoperative replacement therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The study evaluated the e icacy of suturing and the e ect of warfarin on prevention of post-extraction bleeding. Ak 2012;Carter 2003;Howard 1973;Henderson 1998;Pinsent 1986; CTRI/2017/09/009784; NCT02918045; NCT03108365 and Zhou 1985 were preventive trials. Kjellman 1973 assessed pain management a er removal of impacted third molars.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…The study evaluated the e icacy of suturing and the e ect of warfarin on prevention of post-extraction bleeding. Ak 2012;Carter 2003;Howard 1973;Henderson 1998;Pinsent 1986; CTRI/2017/09/009784; NCT02918045; NCT03108365 and Zhou 1985 were preventive trials. Kjellman 1973 assessed pain management a er removal of impacted third molars.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…These findings are in accordance with previously reported figures, which range from 1.9% to 31.5%. 6,7,10,14,15 However, the discrepancy between reported values may relate to the use of different definitions of post-extraction bleeding. A retrospective study using the same definition for post-extraction bleeding as in this study reported that the incidence of post-extraction bleeding for patients receiving anticoagulants and those not receiving anticoagulants was no more than 11% and 0.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our multivariate logistic regression analysis revealed that use of mouth splints significantly decreased the risk of post-extraction bleeding in haemophilia patients. Previous literature and guidelines have recommended the use of mouth splints in haemophilia patients 3,4,10,13 and patients on antithrombotic therapy, 18 because it prevents the tongue from scratching the inside of the extraction socket and protects the blood clot beneath it. However, we believe our study is the first to have used statistical methods to support the preventive effect of mouth splints J o u r n a l P r e -p r o o f for post-extraction bleeding in haemophilia patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fibrin glues [4], collagen adhesives [5,6]), synthetic and semi-synthetic (gelatin-resorcinol-formaldehyde [7], cyanoacrylates [8]) and biomimetics (marine mussel extracts [9]). However, the use of blood derived products such as fibrin has been associated with the risk of diseases transmission, while cyanoacrylates degrade into formaldehyde, which confines their use to external applications [1,10,11]. One possible solution to circumvent these limitations is the development of adhesives based on biodegradable and biocompatible polymers.…”
Section: Introductionmentioning
confidence: 99%